1986
DOI: 10.1055/s-2008-1048863
|View full text |Cite
|
Sign up to set email alerts
|

Knochenmarkszintigraphie mit Radiokolloiden bei Skelettmetastasen

Abstract: The sensitivity and specificity of bone marrow scintigraphy in demonstrating skeletal metastases was examined in 40 patients with focal metastases. Radiology and MDP scintigraphy were used as reference methods. Sensitivity depends on the region of the skeleton. False negatives are the rule in parts of the skeleton containing little bone marrow. In relation to the entire bone marrow content, sensitivity is 0.64. The high proportion of false negatives (36%) in the presence of confirmed metastases and the incompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Marrow scanning is traditionally believed to be of little use for evaluating patients with suspected metastases (Datz and Taylor 1985;Fritz et al 1986). Thus, Fritz et al reported a sensitivity of 64% of bone marrow scans in 36 patients with solid carcinomas and in 4 pa- Fig.…”
Section: Metastatic Turnoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Marrow scanning is traditionally believed to be of little use for evaluating patients with suspected metastases (Datz and Taylor 1985;Fritz et al 1986). Thus, Fritz et al reported a sensitivity of 64% of bone marrow scans in 36 patients with solid carcinomas and in 4 pa- Fig.…”
Section: Metastatic Turnoursmentioning
confidence: 99%
“…Thus, Fritz et al reported a sensitivity of 64% of bone marrow scans in 36 patients with solid carcinomas and in 4 pa- Fig. a Normal bone scan with clear defect on the immunomarrow scan in lung cancer (b) tients with Hodgkin's disease or NHL (Fritz et al 1986). a Normal bone scan with clear defect on the immunomarrow scan in lung cancer (b) tients with Hodgkin's disease or NHL (Fritz et al 1986).…”
Section: Metastatic Turnoursmentioning
confidence: 99%
“…Especially bone métas tasés in prostatic cancer were studied with both conven tional bone scintigraphy and nanocolloid bone marrow scintigraphy leading to equivocal results. While some studies indicated that bone marrow scintigraphy may be more specific than bone scintigraphy in detecting skeletal métastasés (81 vs. 73%) [11], sensitivity seemed to be decreased compared to conventional bone scintigraphy in patients with prostatic cancer (83 vs. 86%) [11,12], Simi lar results were obtained for different metastatic tumours including breast cancer, lung cancer and cancer of the thy roid gland, with bone marrow imaging reaching a 64-77% sensitivity in detecting métastasés of the skeleton [13][14][15], More recently, bone marrow immunoscintigraphy using anti-NCA-95 MAbs has proved to be superior to bone marrow scintigraphy using serum albumin nanocolloids in detecting bone marrow métastasés of lymphoma, breast carcinoma and small-cell bronchogenic carcinoma [2], In this study, bone scintigraphy was abnormal in 17 out of 30 patients compared to 24 patients with abnormal bone marrow scans and bone marrow immunoscans. Compared to bone marrow scans using serum albumin nanocolloids, additonal 28 marrow lesions were detected by bone marrow immunoscintigraphy; 80% of these addi tional lesions were confirmed as tumours by marrow biopsy or radiologic examinations like plain film radiog raphy, computed tomography or magnetic resonance imaging.…”
Section: Resultsmentioning
confidence: 64%
“…Im Gegensatz zu den Befunden der vorgelegten Studie berichteten mehrere Autoren beim Prostatakarzinom, Mammakarzinom und anderen soliden Primärtumoren über eine höhere Sensitivität der Skelettszintigraphie im Vergleich zur konventionellen Mikrokolloid-Szintigraphie (10,11). Hotzeet al (15) sowie Sacchi et al (37) und Otsuka et al (27) berichteten, daß die Knochenmarkszintigraphie gelegentlich hilfreich zur Differenzierung benigner von malignen, im Skelettszintigramm nachweisbaren Herdbefunden war, und schlössen, daß beide szintigraphischen Methoden einander in ihrem Informationsgehalt ergänzen.…”
Section: Ergebnisseunclassified